APLIKASI BEBERAPA DOSIS HERBISIDA PARAQUAT PADA BIDURI DENGAN UMUR YANG BERBEDA - Gina Erida (Jurnal Floratek, 2010)
The study on application of different dosages of paraquat herbicide on different ages of milkyweed (Calotropis gigantea R. Br) have been conducted in Experimental Station, Agriculture Faculty, Syiah Kuala University, Darussalam Banda Aceh. The treatments were arranged in a Completely Randomized Design (CDR) with two factors. The first factor was dosages of herbicide which were 0; 0,1; 0,2; 0,3; and 0,4 kg active ingredient (a.i.) ha-1. The second factor was ages of  C. gigantea R. Br which were 30 days, 45 days and 60 days after planting. The result showed that dosage of 0,3 kg i.a. ha-1 significantly increased the percentage of C. gigantea R. Br and decreased the dry weight shoot and root of C. gigantea R. Br. The youngest stage of C. gigantea R. Br was more effective to be controlled, and had a lower dry weight shoot and root than the oldest one. The paraquat herbicides applied with dosages of 0,3 kg a.i. ha-1 on 30 days after planting increased the percentage of C. gigantea R. Br, and  reduced shoot and root dry weight of C. gigantea R. Br.